Efficacy of different traditional Chinese medicine decoctions in the treatment of ischemic stroke: a network meta-analysis - Ning, Baicheng; Zhu, Xiaoting; Wu, Xiaodong; Zhu, Weiyao; Wang, Runze; Qi, Chang; Li, Mingquan (Frontiers in Pharmacology, 2024)
Objective: Currently, traditional Chinese medicine (TCM) and its combinations are widely used in the treatment and rehabilitation of patients with ischemic stroke.However, current studies should mainly focus on the therapeutic effects of traditional Chinese medicines alone. This paper will employ a network meta-analysis to compare the efficacy of different TCM decoctions in the treatment of patients with ischemic stroke.Methods: Chinese and English databases including PubMed, Embase, Cochrane Library, and Web of Science were searched to collect randomized controlled trials of TCM decoctions in the treatment of patients with ischemic stroke (IS), with a search time frame until April 2024. A library of references was created using EndNote 21.Quality assessment was performed using the Version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB 2). A Bayesian network meta-analysis of data was performed using R4.3.1 and STATA 15.0.Results: A network meta-analysis was conducted on 119 randomized controlled trials including 12137 IS patients. The following TCM decoctions were involved: Xinglou Chengqi Decoction (XLCQD), Shenqi Tongluo Decoction (SQTLF), Zhongfeng Jiuxian Decoction (ZFJXD), Yiqi Tongluo Decoction (YQTLD), Tongqiao Huoxue Tang (TQHXT) , Tongluo Xifeng Decoction (TLXFD), Tongluo Fuzheng Decoction (TLFZD), Xuefu Zhuyu Decoction (XFZYD), Xiaoxuming Decoction (XXMD), Qufeng Xingxue Tongluo Formula (QFXXTLF) , Banxia Baizhu Tianma Decoction (BXBZTMD), Buyang Huanwu Tang (BYHWT) ,Huatan Tongluo Decoction (HTTLD), Yiqi Huoxue Tongluo Decoction (YQHXTLD), Yiqi Huoxue Decoction (YQHXD), and Yiqi Huoxue Kaiqiao Prescription (YQHXKQP). Of them, XFZYD was most effective in reducing the NIHSS score; SQTLF was most effective in increasing the Barthel Index (BI) score; and HTTLD was most effective in improving activities of daily living (ADL).This network meta-analysis provided data on the relative efficacy of different TCM decoctions. Of them, XFZYD was most effective in reducing the NIHSS score; SQTLF was most effective in increasing the BI score; and HTTLD was most effective in improving the ADL score. At the same time, overall, XFZYD ranked first with its best efficacy regarding all the three outcome measures above, and SQTLF came second with its impact on two of the outcome measures.